Gafchromic EBT‐XD film: Dosimetry characterization in high‐dose, volumetric‐modulated arc therapy. (8th November 2016) - Miura, Hideharu; Ozawa, Shuichi; Hosono, Fumika; Sumida, Naoki; Okazue, Toshiya; Yamada, Kiyoshi; Nagata, Yasushi
Abstract : Radiochromic films are important tools for assessing complex dose distributions. Gafchromic EBT‐XD films have been designed for optimal performance in the 40–4, 000 cGy dose range. We investigated the dosimetric characteristics of these films, including their dose‐response, postexposure density growth, and dependence on scanner orientation, beam energy, and dose rate with applications to high‐dose volumetric‐modulated arc therapy (VMAT) verification. A 10 MV beam from a TrueBeam STx linear accelerator was used to irradiate the films with doses in the 0–4, 000 cGy range. Postexposure coloration was analyzed at postirradiation times ranging from several minutes to 48 h. The films were also irradiated with 6 MV (dose rate (DR): 600 MU/min), 6 MV flattening filter‐free (FFF) (DR: 1, 400 MU/ min), and 10 MV FFF (DR: 2, 400 MU/min) beams to determine the energy and dose‐rate dependence. For clinical examinations, we compared the dose distribution measured with EBT‐XD films and calculated by the planning system for four VMAT cases. The red channel of the EBT‐XD film exhibited a wider dynamic range than the green and blue channels. Scanner orientation yielded a variation of ∼ 3 % in the net optical density (OD). The difference between the film front and back scan orientations was negligible, with variation of ∼ 1.3 % in the net OD. The net OD increased sharply within the first 6 hrs after irradiation and gradually afterwards. No significant difference was observed for the beam energy and dose rate, with a variation of ∼ 1.5 % in the net OD. The gamma passing rates (at 3%, 3 mm) between the film‐ measured and treatment planning system (TPS)‐calculated dose distributions under a high dose VMAT plan in the absolute dose mode were more than 98.9%. PACS number(s): 87.56 Fc